1998
DOI: 10.1007/bf02751701
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of warm water from the Kuroshio Extension into the Perturbed Area

Abstract: The path of the Kuroshio Extension describes two stationary meanders with crests at approximately 144°E and 150°E. The short-term meridional fluctuations of the warm water spreading northward from the first crest at the surface and its vertical structure were analyzed by using 5-day-mean surface temperature maps published by JAFIC, monthly 100-m-depth temperature maps edited by the JMA, and CTD data obtained by the R.Vs. Kofu-Maru, Hakuho-Maru and Tansei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In June, the Oyashio and Kuroshio fronts are defined by the 5°C isotherm at 100 m depth and 14°C isotherm at 200 m depth, respectively. 23,24 These observations together with closely located towing sites suggest that oceanographic conditions for all tows were almost identical and located within the KOTZ.…”
Section: Resultsmentioning
confidence: 87%
“…In June, the Oyashio and Kuroshio fronts are defined by the 5°C isotherm at 100 m depth and 14°C isotherm at 200 m depth, respectively. 23,24 These observations together with closely located towing sites suggest that oceanographic conditions for all tows were almost identical and located within the KOTZ.…”
Section: Resultsmentioning
confidence: 87%
“…Both Pickart et al (1999) and Kuroshio branching observations by Sainz-Tra Âpaga and Sugimoto (1998Sugimoto ( , 1999) support this assumption. Over 60% of these drifters move down the large-scale dynamic height ®eld as they meander out into the Paci®c.…”
Section: Large-scale Branchingmentioning
confidence: 81%
“…This assumes the branching and ring formation involve a similar thickness of¯uid. Both Pickart et al (1999) and Kuroshio branching observations by Sainz-Tra Âpaga and Sugimoto (1998Sugimoto ( , 1999) support this assumption. Subtracting the streamer estimate above gives a branching estimate of 2.6´10 14 m 3 year ±1 .…”
Section: Large-scale Branchingmentioning
confidence: 81%
See 1 more Smart Citation
“…[] suggested that small meanders are important to the generation of streamers. Indeed, the KE emits its warm water to the north near the first crest of the quasi‐stationary KE meander with a period of 20–40 days [ Sainz‐Trapaga and Sugimoto , ], which is roughly consistent with the small meander periods of 6–40 days observed from the KESS array [ Tracey et al ., ]. Warm‐water streamers are important routes for the northward migration of warm‐water fish toward the feeding area north of the KE [ Sugimoto and Tameishi , ] and have also been considered a possible source of a quasi‐stationary jet flowing northeastward across the Kuroshio‐Oyashio transition area [ Isoguchi et al ., ; Wagawa et al ., ].…”
Section: Introductionmentioning
confidence: 99%